Comparison of Economic Cycles of the Slovak Economy and Other Visegrad Four Countries - Matoušková, Eleonora (Public Finance Quarterly, 2022)
The aim of the article is to compare the course of economic cycle in the Slovak economy with the economic cycles of the other three Visegrad Four (V4) countries for the period 2003–2021. The comparison was carried out on the basis of monitoring gross domestic product, unemployment rate and the individual components of aggregate demand developments. In the period reviewed, we saw three phases of economic growth and two phases of economic downturn in these countries. The first economic crisis caused by the global financial crisis occurred in the V4 countries in 2009. GDP decreased the most in Hungary, slightly less in Slovakia and the Czech Republic. The economic downturn avoided Poland, where there was only a slowdown in growth. In 2020, the economies of all V4 countries were affected by the coronavirus crisis, with real GDP falling in each of them. In the Slovak Republic, Hungary and the Czech Republic, the decrease in GDP was around 5 per cent, in Poland it was less (–2.7%). The measures taken by governments and the improvement of the health situation helped to revive the growth of the economies of the V4 countries in 2021.